2018
DOI: 10.1093/fampra/cmy087
|View full text |Cite
|
Sign up to set email alerts
|

Patient cardiovascular risk self-management: results from a randomized trial of motivational interviewing delivered by practice nurses

Abstract: Background To enhance cardiovascular risk management and patients’ self-management, a tailored programme to improve cardiovascular risk management was tested in a randomized trial. The presented study concerned secondary analysis. Objectives To explore the correlations of practice nurses’ counselling skills at baseline on chronic illness care (measured with Patient Assessment of Chronic Illness Care questionnaire) and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Despite these MI interventions, there is variability in how communication about behaviour change is enacted in primary care (Noordman et al., 2012). Research examining GPNs’ use of MI has focused on their experiences, self‐perceived use, training, or quantitative analysis of the technique (Huntink, Koetsenruijter, Wensing, & Lieshout, 2019; Östlund, Wadensten, Häggström, & Kristofferzon, 2014; Östlund, Kristofferzon, Häggström, & Wadensten, 2016; Östlund, Wadensten, Kristofferzon, & Häggström, 2015). This study aimed to address a gap in the research through qualitative examination of how GPNs support lifestyle risk reduction with patients during chronic disease consultations using MI techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these MI interventions, there is variability in how communication about behaviour change is enacted in primary care (Noordman et al., 2012). Research examining GPNs’ use of MI has focused on their experiences, self‐perceived use, training, or quantitative analysis of the technique (Huntink, Koetsenruijter, Wensing, & Lieshout, 2019; Östlund, Wadensten, Häggström, & Kristofferzon, 2014; Östlund, Kristofferzon, Häggström, & Wadensten, 2016; Östlund, Wadensten, Kristofferzon, & Häggström, 2015). This study aimed to address a gap in the research through qualitative examination of how GPNs support lifestyle risk reduction with patients during chronic disease consultations using MI techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Laurant et al, experiences of chronic illness care in patients with established CVD or at high CVD risk did not change after the implementation of a tailored program aiming at nurses’ counseling skills [ 33 ]. On the other hand, a Cochrane systematic review by Huntink et al suggested that appropriately trained nurses can provide care of the same quality as primary care doctors and achieve similar health outcomes for patients [ 34 ]. While patient health outcomes were similar for nurses and doctors, patient satisfaction was higher with nurse-led care because nurses tended to provide longer consultations, give more information to patients, and recall patients more frequently than doctors.…”
Section: Discussionmentioning
confidence: 99%